Robust Watermarking Scheme Using Wave Atoms. (19th September 2010) - Leung, H. Y.; Cheng, L. M.
Abstract : A robust blind watermarking scheme using wave atoms is proposed. The watermark is embedded in the wave atom transform domain by modifying one of the scale bands. The detection and extraction procedures do not need the original host image. We tested the proposed algorithm against common image processing attacks like JPEG compression, Gaussian noise addition, median filtering, and salt and pepper noise, and also compared its performance with other watermarking schemes using multiscale transformation. They were carried out using Matlab software. The experimental results demonstrate that the proposed algorithm has great robustness against various imaging attacks.